Shoot Organogenesis and Plant Regeneration from Leaf Explants of Lysionotus serratus D. Don - Qiansheng Li; Min Deng; Jie Zhang; Wei Zhao; Yigang Song; Quanjian Li; Qingjun Huang (The Scientific World Journal)
The gesneriaceous perennial plant, Lysionotus serratus, has been used in traditional Chinese medicine. It also has a great development potential as an ornamental plant with its attractive foliage and beautiful flowers. An efficient propagation and regeneration system via direct shoot organogenesis from leaf explant was established in this study. High active cytokinin (6-benzyladenine (BA) or thidiazuron (TDZ)) was effective for direct organogenesis of initial induction. Murashige and Skoog (MS) growth media containing 0.5 mg L−1 BA alone or with combination of 0.1 mg L−1  α-Naphthaleneacetic acid (NAA) were the most effective for shoot proliferation. High BA concentration (1.0 mg L−1) in the media caused high percentage of vitrified shoots though they introduced high shoot proliferation rate. Histological observation indicated that adventitious shoot regeneration on the medium containing 0.5 mg L−1 BA alone occurred directly from leaf epidermal cells without callus formation. Regenerated shoots rooted well on medium containing half-strength MS medium with 0.5 mg L−1 indole-3-butyric acid (IBA) and indole-3-acetic acid (IAA), and the plantlets successfully acclimatized and grew vigorously in the greenhouse with a 94.2% and 92.1% survival rate.